Indirect Traumatic Optic Neuropathy Following Head Injury: Report of Five Patients and Review of the Literature - Miliaras, Georgios; Fotakopoulos, George; Asproudis, Ioannis; Voulgaris, Spyridon; Zikou, Anastasia; Polyzoidis, Konstantinos (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Indirect traumatic optic neuropathy (ITON) is a rare occurrence in patients with head injuries, mostly affecting young people. Loss of vision is a feared consequence. Its natural history and optimal care remain undetermined. Randomized controlled studies are missing. Treatment alternatives include mere observation, corticosteroid administration, or surgical decompression of the optic canal. Among these options, an individual approach is considered.Case Reports We report five patients with head injury and ITON: a 63-year-old woman was left permanently blind after a fall; a 33-year-old man lost his vision of the left eye immediately after a car accident; and three young men (aged 26, 21, and 22 years) who were intubated after a road accident noted loss of vision from one eye after they became conscious. The 26-year-old patient in the last group regained his sight 1 month later, whereas the other two never had it returned. All of our patients were treated conservatively: Methylprednisolone was administrated.Conclusion Patients with ITON are managed on an individual basis. Informed consent must be obtained for mere observation or administration of corticosteroids and/or optic canal decompression. The natural history of this disorder is unknown. Only randomized controlled studies can fix standard guidelines of care. Preventive measures to decrease the incidence of head injured patients are mandatory.
Keywords: traumatic optic neuropathy; blindness; corticosteroids; optic canal; optic; nerve decompression